Lost clips after targeted lymph node biopsy in breast cancer patients: Follow-up of the CLIP-study. Issue 8 (August 2021) - Hartmann, Steffi; Stachs, Angrit; Gerber, Bernd; Knauerhase, Hellen; Kamin, Frank; Kundt, Günther; Reimer, Toralf
Abstract: Introduction: Clipping and selective removal of axillary lymph nodes in breast cancer patients presenting with initially node-positive disease and achieving a nodal downstaging after primary systemic therapy is a less invasive method for axillary staging. An imaging guided localization and successful extirpation of these clipped lymph nodes is not possible in all patients. To date no follow-up data regarding patients with lost clips are available. Material and methods: The oncological outcome of all participants of the CLIP-study and the results of postoperative axillary imaging in those patients with unproven clip resection are presented. Results: A total of thirty patients were included into the pilot study. In ten of these patients (33%) the removal of the clipped axillary lymph node could not be verified by intraoperative radiograph. Postoperative imaging did not find lost clips in eight of these ten patients (80%). The lost clip was detected in two patients after surgery (20%), by mammography in one patient during routine follow-up and by computed tomography scan in one patient before radiotherapy. After a median follow-up of 40 months, 26 (87%) patients were still alive. Seven patients (23%) developed distant recurrent disease. No local or axillary recurrences were observed. Conclusion: Lost clips were detected by postoperative imaging only in a minority of patients. The impact of lost clips on axillary recurrences in breast cancer patients is still unclear and should be further clarified in larger, multicentric trials.